Pembangunan Sistem Aplikasi Deteksi Code Smell berdasarkan Metrik Feature Envy - Vicky Virdus; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Code Smell is a structural pattern part of a software program code that has a bad design. The code structure pattern that contributes to excessive coupling is code smell feature envy. Feature Envy occurs because of the high coupling of the inaccuracy of class member placement within a class. Incorrect class member placement will affect the program code structure if a change is made. However, the different patterns of perceptions of each programmer resulted in the difficulty of measuring the code smell feature envy. This study aims to equate the perceptions of programmers by building an application system that can detect the envy smell feature code automatically so that it can simplify the implementation of clean code smell feature envy. The application system for detecting the smell feature envy code was developed based on feature envy factor as a reference in measuring and calculating its value. This system has been tested using the White box method for unit testing and integration testing and then the Black Box method for validation testing with pass status or valid for each method that has been applied. This system also gets 100% accuracy rate for each project tested.